Ernest Hemingway's the Oldman and the Sea : A Tale of Man's Helplessness Agaist Destiny (Global Journal of Human-Social Science, 2020)
Earnest Hemingway, an American writer, produced considerable novels in the history of English literatutre. Hemingway's The Oldman and the Sea is a story of oldman's struggle and his helplessness against destiny. Like Greek tragedians, Hemingway accepts the harshness of destiny in man's life. It is very well said "Man proposes and God disposes" that clearly denotes the role of destiny in man's life. The story of The Oldman and the Sea is universal because it reveals how human beings struggle to get something in life but sometimes crushed under the wheels of destiny. The old man has indomitable spirit and sea experience yet he is unable to catch the fish for a few days. One day, he caught the big fish called the Marlin but it was too big for him to drag to the shore. The Old man tried to drag the Marlin to the shore but in a midway its blood attracted the Sharks and he brought only its skeleton on the shore. So Hemingway talks about the helplessness of man against destiny through the character of an old man. This paper is a sincere effort to display man's helplessness against destiny through the character of old man.